2009
DOI: 10.1074/jbc.m808166200
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Renders Retinal Pigment Epithelial Cells Susceptible to Complement-mediated Injury

Abstract: Uncontrolled activation of the alternative pathway of complement is thought to be associated with age-related macular degeneration (AMD). The alternative pathway is continuously activated in the fluid phase, and tissue surfaces require continuous complement inhibition to prevent spontaneous autologous tissue injury. Here, we examined the effects of oxidative stress on the ability of immortalized human retinal pigment epithelial cells (ARPE-19) to regulate complement activation on their cell surface. Combined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
168
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 165 publications
(191 citation statements)
references
References 28 publications
10
168
1
2
Order By: Relevance
“…It has previously been reported that doses of up to 1 mM are not cytotoxic, and do not lead to disruption of barrier function in these cells (19). After treatment with H 2 O 2 , monolayers were immediately exposed to 25% NHS as a source of complement proteins (18).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has previously been reported that doses of up to 1 mM are not cytotoxic, and do not lead to disruption of barrier function in these cells (19). After treatment with H 2 O 2 , monolayers were immediately exposed to 25% NHS as a source of complement proteins (18).…”
Section: Methodsmentioning
confidence: 99%
“…FBS was removed completely for the final 5-7 days (2-3 media changes) prior to measurements, which we have previously shown does not alter survival or monolayer formation in these cells (29). TER of the cell monolayer on the Transwell filters was determined by measuring the resistance across the monolayer with an EVOM volt-ohmmeter (World Precision Instruments) (18). The value for cell monolayers was determined by subtracting the TER for filters without cells and then multiplying by the surface area of the filters.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations